Guidelines for Utilizing Marketing Innovations to Create Sustainable Competitive Advantages for the Thai Cosmetic Industry - Theerachoksawat, Kitsikarn; Thanawatparinya, Kanecha; Silpcharu, Thanin (Journal of Posthumanism, 2025)
The purpose of this research is to develop a structural equation model to utilize marketing innovation to build a sustainable competitive advantage for Thai cosmetic industry businesses. Qualitative research included in-depth interviews and group discussions with experts, and quantitative research was conducted through questionnaire data collection from 500 business executives. The analysis included descriptive, inferential, and multivariate statistical analyses. The research findings identify the approaches to using marketing innovation to establish a sustainable competitive advantage for Thai cosmetic industry businesses, with four priorities identified: 1) Media Innovation ( = 4.33): The most important aspect is designing a website that is user-friendly and easy to contact. 2) Management Innovation ( = 4.31): The most important item is using QR codes to facilitate customers. 3) Product Innovation ( = 4.30): The most important item is improving product components to meet market demands. 4) Information Innovation ( = 4.22): The most important item is controlling data security. The results of the comparison test showed that medium and small businesses placed more importance on using marketing innovation to create a sustainable competitive advantage for the Thai cosmetic industry than large businesses, with statistical significance at the 0.05 level. The results of the analysis of the developed structural equation model indicated that it was consistent with the empirical data, with a chi-square probability level of 0.061, a relative chi-square of 1.151, a fit index of 0.957, and a root mean square error of approximation (RMSEA) of 0.017.